1965
DOI: 10.1590/s0006-87051965000100038
|View full text |Cite
|
Sign up to set email alerts
|

Absorção de nutrientes pela cultura do arroz

Abstract: Com a finalidade de determinar a marcha da absorção dos nutrientes essenciais pela cultura do arroz (Oryza sativa L.). conduziu-se um ensaio em casa de vegetação, em vasos de Mitscherlich. Cada 10 dias, colhiam-se plantas, para análise de N, P, K, Ca e Mg. Verificou-se que, para a produção de 4.300 kg de grãos em casca e 39.350 kg de palha e raízes por hectare, seriam absorvidos 115 kg de N, 18,5 kg de P, 142 kg de K, 35 kg de Ca e 36 kg de Mg. O nitrogênio e o potássio foram, na totalidade, absorvidos até 110… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
6

Year Published

1973
1973
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 2 publications
0
4
0
6
Order By: Relevance
“…The maximum accumulation of N in the shoots was later and occurred from 95 to 110 DAE, but with the maximum uptake rates occurring after 65 DAE (Figures 2d and 2f). Gargantini and Blanco (1965) also observed that the maximum accumulation of N in the rice shoots occurred at around 110 DAE. Phosphorus was the only nutrient to be accumulated at an increased rate in the shoots up to the end of the cycle, which shows that its uptake occurred practically throughout the crop cycle (Figure 3d), which was also observed by Gargantini and Blanco (1965).…”
Section: Brs Primavera Maravilhamentioning
confidence: 69%
See 3 more Smart Citations
“…The maximum accumulation of N in the shoots was later and occurred from 95 to 110 DAE, but with the maximum uptake rates occurring after 65 DAE (Figures 2d and 2f). Gargantini and Blanco (1965) also observed that the maximum accumulation of N in the rice shoots occurred at around 110 DAE. Phosphorus was the only nutrient to be accumulated at an increased rate in the shoots up to the end of the cycle, which shows that its uptake occurred practically throughout the crop cycle (Figure 3d), which was also observed by Gargantini and Blanco (1965).…”
Section: Brs Primavera Maravilhamentioning
confidence: 69%
“…Gargantini and Blanco (1965) also observed that the maximum accumulation of N in the rice shoots occurred at around 110 DAE. Phosphorus was the only nutrient to be accumulated at an increased rate in the shoots up to the end of the cycle, which shows that its uptake occurred practically throughout the crop cycle (Figure 3d), which was also observed by Gargantini and Blanco (1965). Nevertheless, there are periods in the cycle in which the cultivars take up P at higher rates, as may be seen in the high P uptake rates of the BRS Primavera cultivar at 70 DAE and of the cultivars Caiapó and Maravilha after 90 DAE (Figure 3f).…”
Section: Brs Primavera Maravilhamentioning
confidence: 69%
See 2 more Smart Citations
“…Independentemente dos tratamentos utilizados, o cultivar IAC 201 apresentou, nos dois anos de cultivo, a seguinte ordem decrescente de exigência de macronutrientes no período de florescimento: N > K > Ca > Mg > P > S, bastante semelhante à observada por Gargantini & Blanco (1965), N > K > Ca > Mg > P, e diferente das seqüências relatadas por Fageria et al (1997) Crusciol et al (1999), para o cultivar IAC 201 no sistema de sequeiro, N > K > Mg > Ca > P > S.…”
Section: Resultsunclassified